(untitled) (Physical Education, Health and Social Sciences, 2025)
This study investigates the effect of Green Inclusive Leadership (GIL) on Green Creativity (GC) through the mediating roles of Green Innovative Climate (GIC) and Green Thinking (GT) within manufacturing industries. The research aims to understand how leadership behaviors that emphasize inclusiveness and environmental responsibility foster creativity among employees to achieve sustainable organizational outcomes. The study collected data through a quantitative survey design which included 335 participants who worked in manufacturing industries. The researchers used structured questionnaires to assess GIL and GC and GIC and GT. The study confirmed reliability and validity through testing with Cronbach’s alpha and KMO/BTS assessments. This research conducted hypothesis testing through SPSS with Hayes’ PROCESS Macro Model 4 which used regression and mediation analyses together with bootstrapping methods. The results show that GIL positively influences green creativity. The relationship between GIC and GT shows partial mediation because inclusive leadership directly boosts creativity while creating organizational support systems that develop sustainability-based thinking processes. The study provides actionable insights for manufacturing managers, who need to develop inclusive leadership skills and create a sustainable green business environment while teaching employees sustainable business practices. The practices enable organizations to integrate sustainability into their daily operations while satisfying both regulatory requirements and stakeholder expectations. This research extends existing literature by simultaneously examining two mediators’ organizational climate and cognitive orientation in the leadership-creativity relationship within manufacturing industries. The study presents new empirical data together with a dual mediation framework which enhances both theoretical knowledge and practical uses of sustainability leadership.